Potensi Anti-Inflamasi Senyawa Crotalaria Medicaginea terhadap COX-2: Studi In Silico - Najla Dhifa Tofanny; Fitri Amelia (MASALIQ, 2026)
This study was motivated by the limited number of in silico investigations examining the anti-inflammatory potential of bioactive compounds from Crotalaria medicaginea Lamk, despite the fact that inflammation is a pathological condition largely mediated by the cyclooxygenase-2 (COX-2) enzyme. The study aimed to analyze the potential interactions and binding affinities of bioactive compounds from Crotalaria medicaginea Lamk toward COX-2 as an anti-inflammatory target. A computational research design was employed using an in silico molecular docking approach. The research samples comprised the COX-2 enzyme structure obtained from the Protein Data Bank and bioactive compounds identified from the phytochemical data of Crotalaria medicaginea Lamk. Data were generated through ligand and protein preparation and subsequently analyzed using docking software to determine binding energy values and interaction patterns of amino acid residues at the active site of the enzyme. The results showed that one of the bioactive compounds exhibited stable binding affinity and was able to form interactions at the COX-2 active site, thereby supporting the theory that COX-2 inhibition can attenuate inflammatory responses. The study concludes that the bioactive compounds of Crotalaria medicaginea Lamk have the potential to be developed as anti-inflammatory candidates, with theoretical implications for enriching the literature on the use of medicinal plants based on in silico studies and practical implications as a basis for developing natural anti-inflammatory drugs. This research also opens up opportunities for further in vitro and in vivo studies to confirm the computational findings.